The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1516-35982011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Levels of digestible methionine+cystine in diets for high genetic potential barrows from 95 to 125 kg

Abstract: This study was carried out to evaluate the effects of increasing levels of digestible methionine+cystine on performance and carcass composition of high genetic potential barrows for lean deposition. Sixty-four barrows with initial weight of 95.46 ± 1.09 kg were allotted to a completely randomized block design, with four levels of digestible methionine+cystine (0.427, 0.466, 0.504, and 0.545%, corresponding to the digestible methionine+cystine:digestible lysine ratios of 57.0, 62.0, 67.0 and 73.0%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…On the contrary, a Met deficiency in pigs can lead to lower DWG (Conde-Aguilera et al, 2014), growth suppression of the intestinal mucosa, reduction of intestinal epithelium, and increase of oxidative stress (Bauchart-Thevret et al, 2009;Chen et al, 2014). Several studies have showed that pigs can tolerate some Met deficiency (Santos et al, 2011;Ying et al, 2015) or excess levels in the diet (Pena et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, a Met deficiency in pigs can lead to lower DWG (Conde-Aguilera et al, 2014), growth suppression of the intestinal mucosa, reduction of intestinal epithelium, and increase of oxidative stress (Bauchart-Thevret et al, 2009;Chen et al, 2014). Several studies have showed that pigs can tolerate some Met deficiency (Santos et al, 2011;Ying et al, 2015) or excess levels in the diet (Pena et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Methionine (Met) is the second or thirdlimiting aminoacid (AA) in conventional diets for growing pigs, which can lead to its deficiency, reduced availability for protein synthesis and limited growth (Bauchart-Thevret et al, 2009;NRC, 2012;Chen et al, 2014). The Met levels present in most dietary ingredients for pigs are insufficient; thus, it must be provided from a synthetic source (Santos et al, 2011). Additionally, bioavailability and bioefficacy of synthetic DL-Met isomers show inconsistent results in growth performance of pigs (Shen et al, 2014;Kong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition potassium citrate is usually taken as a drug for reducing renal acidosis [99]. In food, animal proteins containing methionine like meat break down into cystines which increase urinary cystine level in the body [100]. In a study it was shown that urinary cysteine excretion reduced to 34% by consuming very low protein diet nearly 20g/day [101].…”
Section: Cystine Stonementioning
confidence: 99%
“…Cysteine (Cys) is included in the structure of many proteins, linking polypeptide chains as a precursor of taurine and glutathione (Baker, 1991). Most Cys must be obtained from dietary Met since many feed ingredients lack of adequate Cys levels (Santos et al, 2011). Thus, Met should be added into pig diets to meet the methionine+cysteine (Met+Cys) complex requirement.…”
Section: Introductionmentioning
confidence: 99%